Evaluation of childrens' play. Tools and methods - Bulgarelli, Daniela (De Gruyter, 2018)
This book is one of the outcomes of the COST Action TD139 "LUDI - Play for Children with Disabilities" (2014-2018), a multidisciplinary network of European researchers and practitioners devoted to the theme of play from different perspectives. This book contributes to the LUDI reflection about play, by reviewing the existing knowledge on play evaluation and by presenting tools and methodologies for play assessment.